Molecular epidemiology and environmental persistence of methicillin-resistant coagulase-positive Staphylococci in a Veterinary Teaching Hospital in Thailand: Evidence for nosocomial transmission and One Health implications - Punpichaya Fungwithaya; Jayaseelan Murugaiyan; David J. Hampson; Nuvee Prapasarakul (Veterinary World, 2025)
Background and Aim: (MRSC), are emerging zoonotic pathogens in veterinary hospitals, posing significant infection control challenges. This study aimed to investigate the molecular epidemiology, antimicrobial resistance profiles, and clonal dissemination of MRCoPS across environmental surfaces, veterinary personnel, and canine patients at the Veterinary Teaching Hospital, Chulalongkorn University (VTH-CU), Thailand. Materials and Methods: ) PCR and pulsed-field gel electrophoresis (PFGE). Multivariate logistic regression identified environmental predictors of MRCoPS contamination. Results: elements. PFGE revealed clonal similarity (pattern A) between canine and environmental isolates, confirming the potential for nosocomial transmission. Conclusion: MRCoPS, particularly MRSP, were widely distributed and persistent in the VTH-CU environment, despite routine cleaning. The clonal overlap among environmental and canine isolates highlights potential cross-contamination within the hospital. Strengthened disinfection protocols, antimicrobial stewardship programs, and regular environmental surveillance are imperative to mitigate the spread of multidrug-resistant staphylococci. This study highlights the importance of integrating environmental, animal, and human infection control practices in veterinary facilities within the context of One Health.
Keywords: Antimicrobial Resistance in Staphylococcus; Milk Quality and Mastitis in Dairy Cows; Clostridium difficile and Clostridium perfringens research